Brand Image and Celebrity Endorser on Customer Satisfaction and Customer Loyalty of Scarlett Whitening Body Serum - Amin, Amirudin M.; Sagala, Nova Elisa (First Ciera Publisher, 2025)
This study aims to analyze the influence of Brand Image and Celebrity endorser on Customer Satisfaction and Customer Loyalty of Scarlett Whitening Body Serum in Pekanbaru City. The population in this study was all users of Scarlett Whitening Body Serum in Pekanbaru City, whose number could not be known with certainty, so by using the Roscoe formula, the sample was set at 120 respondents with a purposive sampling method, which is part of nonprobability sampling. Based on the Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS), the results showed that brand image had a positive and significant effect on customer satisfaction, celebrity endorser had a positive and insignificant effect on customer satisfaction, brand image had a positive and insignificant effect on customer loyalty, customer satisfaction had a positive and significant effect on customer loyalty.